Approcci controversi all’unificazione politica italiana prima e dopo il 1861 Un confronto esemplare fra Ippolito Nievo e Federico De Roberto - Artico, Davide (Romanica Silesiana)
The purpose of the article is to compare the best known historical novel by Ippolito Nievo, published in Britain as The Castle of Fratta, to Federico De Roberto’s I Viceré. Nievo drowned to death in 1861, the same year De Roberto was born. The year, which also officially marked the establishment of the Kingdom of Italy, represents a turning point in the history of Italian literature. As the comparison of the two novels shows, the idealistic and optimistic attitude preceding 1861 was to disappear a few years later, as it became apparent that the upper classes lacked the competence and morality needed to lead the new Kingdom. Key words: Ippolito Nievo, Federico De Roberto, historical novel, Risorgimento.